Overkill : Sex and Violence in Contemporary Russian Popular Culture - Borenstein, Eliot, 1966- (Book collections on Project MUSE., 2008)
Perestroika and the end of the Soviet Union transformed every aspect of life in Russia, and as hope began to give way to pessimism, popular culture came to reflect the anxiety and despair felt by many Russians. In 'Overkill' Borenstein explores the lurid and often-disturbing landscape of modern Russian popular culture.